Short-term effects of diabetes on neurosteroidogenesis in the rat hippocampus. Issue 167 (March 2017) - Romano, Simone; Mitro, Nico; Diviccaro, Silvia; Spezzano, Roberto; Audano, Matteo; Garcia-Segura, Luis Miguel; Caruso, Donatella; Melcangi, Roberto Cosimo
Highlights: Short-term diabetes alters hippocampal steroidogenic machinery. Impaired cholesterol homeostasis contributes to altered hippocampal steroidogenesis. Mitochondrial dysfunction contributes to altered hippocampal steroidogenesis. Abstract: Diabetes may induce neurophysiological and structural changes in the central nervous system (i.e., diabetic encephalopathy). We here explored whether the levels of neuroactive steroids (i.e., neuroprotective agents) in the hippocampus may be altered by short-term diabetes (i.e., one month). To this aim, by liquid chromatography–tandem mass spectrometry we observed that in the experimental model of the rat raised diabetic by streptozotocin injection, one month of pathology induced changes in the levels of several neuroactive steroids, such as pregnenolone, progesterone and its metabolites (i.e., tetrahydroprogesterone and isopregnanolone) and testosterone and its metabolites (i.e., dihydrotestosterone and 3α-diol). Interestingly these brain changes were not fully reflected by the plasma level changes, suggesting that early phase of diabetes directly affects steroidogenesis and/or steroid metabolism in the hippocampus. These concepts are also supported by the findings that crucial steps of steroidogenic machinery, such as the gene expression of steroidogenic acute regulatory protein (i.e., molecule involved in the translocation of cholesterol into mitochondria) and cytochrome P450 side chain cleavage (i.e., enzyme converting cholesterol into pregnenolone) and 5α-reductase (enzyme converting progesterone and testosterone into their metabolites) are also affected in the hippocampus. In addition, cholesterol homeostasis as well as the functionality of mitochondria, a key organelle in which the limiting step of neuroactive steroid synthesis takes place, are also affected. Data obtained indicate that short-term diabetes alters hippocampal steroidogenic machinery and that these changes are associated with impaired cholesterol homeostasis and mitochondrial dysfunction in the hippocampus, suggesting them as relevant factors for the development of diabetic encephalopathy.